On the buckling of polymer disks. (March 2019) - Afonso, R.M.; Alves, L.M.; Martins, P.A.F.
Abstract: This paper is focused on the stability of polymer disks subjected to uniform radial edge compression and proposes a methodology to determine the critical pressure at the onset of buckling. The methodology involves the design and fabrication of a tooling system to compress the outer disk surfaces and move material inward in order to apply a uniform radial pressure in the free (unconstrained) volume of the disks. The main objective is to circumvent the application of classical analytical solutions to polymers that exhibit a decrease of the stress-strain curve and negative values of the tangent modulus after initial yielding through determination of the critical pressure at the onset of buckling by matching the experimental and finite element predicted evolutions of the force vs. displacement. A lower bound stress solution is provided to perform a simple and fast conversion of the experimental data into the critical pressure of the polymer disk at the onset of buckling. The results of this investigation can be successfully applied to characterize the forming conditions that give rise to out-of-plane buckling deformation of the polymer centre during the production of a new generation of polymer-metal coins. Highlights: Innovative tool system to compress the outer disk surfaces and move material inward to apply a uniform radial pressure in the free disk volume. New methodology to determine the critical pressure of polymer disks subjected to uniform radial edge compression at the onset of buckling. Lower bound solution to perform a fast conversion of the experimental data into the critical pressure of the polymer disks at the onset of buckling. Potential application of the methodology in the design of a new type of polymer-metal coins.